An AAnalysis of the Thai Government System:: Capitalist Patronage in the Era of Globalization - Mueanjaem, Jakkawarn; Khaomuenwai, Sappaya (King Prajadhipok’s Institute Journal, 2025)
This article analyzes the Thai government system under the context of globalization, emphasizing the relationship between capital and the state, and its impact on the political structure, economy, and quality of democracy in the country. This study examines key concepts of monopoly capital, crony capitalism, and the patronage system in Thai society. The centralization of political power and the absence of effective oversight mechanisms have enabled capital groups to infiltrate and influence the government’s decision-making processes. This results in the allocation of resources that favor specific groups, lack transparency, and contribute to economic and social inequality. The intervention of capital groups manifests across multiple dimensions, including in the legislative, executive, independent organizations, and state enterprises. These interventions occur through mechanisms such as political donations, support for political parties, the appointment of individuals with close ties to capital into key positions, and the manipulation of legal frameworks for private benefit. In addition, foreign capital groups play an important role in shaping national policy through investment, lobbying, free trade agreements, and control of information. This influence contributes to the erosion of Thai state sovereignty and undermines the government’s ability to govern in accordance with the will of the people. Addressing these structural challenges requires comprehensive reform. Legal and administrative reforms must be accompanied by a transformation in political culture-emphasizing decentralization, promoting transparency, creating inclusive spaces for public participation in policy decision-making, and empowering civil society and independent media. Furthermore, reforming the civil service to uphold professional standards, reduce political interference and conflicts of interest, and foster public awareness of citizens’ rights and responsibilities under a democratic regime will be essential. These efforts can help restore public trust and establish a sustainable and democratic political system.